Does Better Provincial Governance Boost Private Investment in Vietnam?. (16th September 2013) - McCulloch, Neil; Malesky, Edmund; Duc, Nhat Nguyen
Summary: A large literature asserts a causal relationship between the quality of economic governance and economic performance. However, attempts to establish such a link at an aggregate level have met with considerable methodological criticism. This paper seeks to overcome this limitation. We match a panel of Vietnamese enterprises from 2006–2010 with a unique panel dataset measuring sub‐national economic governance, and then exploit rules on the terms of local leaders and the mandatory retirement age to try to estimate a causal link between local governance and domestic private investment. With one exception, we do not find a significant relationship between most aspects of local economic governance and private investment. The exception is transparency, which is strongly associated with higher investment, although the weakness of our instruments makes it difficult to determine the size of the effect. Our results have significant implications for policy, given the prevailing assumption that changes in the quality of local economic governance will spur improved economic performance.